REPORT OF THE WORKSHOP TO FORMULATE A STRATEGY FOR THE PACE PROGRAMME - African Union Inter-African Bureau for Animal Resources; AU-IBAR (My University, 2021)
This workshop had been included as an activity of the:first work programme for the Pan-African Programme for the Control of Epizootics (PACE) Common Sendces and Co-ordination Units, but it had been postponed by two months. The dim of the workshop was to draft a PACE strategy document, which, after further refinement, would be presented to the Advisory Committee. The PACE Programme aims to establish and strengthen sustainable epidemiological surveillance of major epizootic diseases and safeguard animal production in Africa. It is a complex programme that covers 32 sub-Saharan countries; it has four major thrusts and six themes, which are represented by the technical units of the Cominon Services. Participants in the workshop included the PACE technical experts and counterparts of the Common Services from Central, Eastern and Western Africa, most of the technical staff of the PACE Co-ordination Units in Bamako and Nairobi, and representatives of the OAU/IBAR and the European Commission. They reviewed the process of strategy development and examined the proposals of each Common Services Unit, using standard criteria to screen for sustainability of programme impacts. The financing agreement for the PACE Programme provides an outline logical framework that orients the programme. It required development to ensure effective project management at national and regional levels. It became evident that, to implement the PACE Programme, close collaboration between Units will be necessary and that this require effective teamwork in planning, implementation, and monitoring. The workshop participants identified problems and constraints likely to arise during the programme. They agreed on a range rernzclial actions, most of which would be undertaken routinely in the course of implementation. Detailed discussions will be held between each Unit and the PCU staff in the preparation of the second year's work programme. The aims of this workshop were partially achieved. It provided the foundation for the development of a coherent strategy for the PACE Programme, and for the development of work programmes, through which the PACE Common Services will provide support to the national PACE programmes. The participants generally regarded the workshop as satisfactory, although there was too little time to finalize the detailed planning of the work programmes ofthe various units. The moderator's report highlights the high workload and the growing concern at the delay in the launch of the PACE Programme, especially at the national level. His recommendations will be taken into account in planning at regional and national levels. In view of the PACE member countries' limited capabilities to develop logical frameworks, it was recommended that the PCU provide assistance, to improve the basis for monitoring and evaluating the programme.
Keywords: Pan-African Control of Epizootics (PACE)